Heaven and earth in the Gospel of Matthew - Pennington, Jonathan T. (Supplements to Novum Testamentum, 2007)
A much-overlooked aspect of the Gospel of Matthew is the theme of heaven and earth. Rather than being a reverential circumlocution for God, 'heaven' in Matthew is part of a highly developed discourse of heaven and earth language. Matthew's idiolectic way of using heaven language consists of four aspects: 1) a distinction in meaning between singular and plural forms of ouranos ; 2) frequent use of the heaven and earth word pair; 3) regular reference to the Father in heaven; and 4) the recurrent use of the Matthean expression, kingdom of heaven. This book examines the historical precedents for each of these aspects and shows in Matthew how they serve one overriding theological purpose: to highlight the tension that currently exists between heaven and earth or God and humanity, while looking forward to its eschatological resolution.